2019
DOI: 10.3899/jrheum.180668
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities in Patients with Rheumatoid Arthritis and Their Association with Patient-reported Outcomes: Results of Claims Data Linked to Questionnaire Survey

Abstract: Objective.To investigate the prevalence of comorbidities in a population-based cohort of persons with rheumatoid arthritis (RA) compared to matched controls and to examine their association with patient-reported outcomes in a survey sample.Methods.Data of 96,921 persons with RA [International Classification of Diseases, 10th ed (ICD-10) M05/M06] and 484,605 age- and sex-matched controls without RA of a German statutory health fund were studied regarding 26 selected comorbidities (ICD-10). A self-reported quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 29 publications
5
32
0
6
Order By: Relevance
“…On the other hand, there are large deviations, e.g. in the degree of DMARD care, which is much higher for rheumatologists in the NDB than in the claims data [28] or in the prevalence of co-morbidity diagnoses [29], which are significantly more frequent in the claims data than in the NDB. Since itis notpossible torule outinsufficient reporting in the NDB as well as over-reporting in insurance data, the authors estimate the information provided by rheumatologists on concomitant diseases in the NDB to be somewhat too low and the claims diagnoses in the insurance data to be somewhat too high.…”
Section: Limitations and Strengths Of The Ndbmentioning
confidence: 99%
“…On the other hand, there are large deviations, e.g. in the degree of DMARD care, which is much higher for rheumatologists in the NDB than in the claims data [28] or in the prevalence of co-morbidity diagnoses [29], which are significantly more frequent in the claims data than in the NDB. Since itis notpossible torule outinsufficient reporting in the NDB as well as over-reporting in insurance data, the authors estimate the information provided by rheumatologists on concomitant diseases in the NDB to be somewhat too low and the claims diagnoses in the insurance data to be somewhat too high.…”
Section: Limitations and Strengths Of The Ndbmentioning
confidence: 99%
“…A particular strength of the PROCLAIR project was therefore the availability of data on people who are not in rheumatological care, but who are treated exclusively by general practitioners or another specialist. The evaluation of comorbidity in RA patients showed that individuals with many comorbidities are less frequently treated by a specialist [14] than individuals with few comorbidities. It could be that in view of the multitude of necessary measures and medications the coordinating function of the general practitioner gains priority.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of health services [4] Comorbidity [14] Physical therapy [9] Income and burden of disease [6] Depressive symptoms and burden of disease [19] Diagnostic delay [18] Provision of health services Extra-articular manifestations Comorbidity The claims data were analysed not only for the PROCLAIR respondents (linking claims and survey data), but also for all insured persons who had one of the three diagnostic codes. Therefore, some analyses refer to the total data set of BARMER insurants (e.g.…”
Section: Costs Of Tnf-alpha Inhibitor Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Совсем недавно А. Luque Ramos и соавт. [65] представили данные анализа коморбидной патологии у 96 921 больного РА (жители Германии). Признаки депрессии были выявлены у 32% опрошенных пациентов, в то время как в контрольной группе (484 605 условно здоровых жителей) лишь у 20%, т. е. почти в 1,5 раза меньше.…”
Section: фак торы влияющие на развитие центральной сенситизацииunclassified